(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
The article discusses and describes methods that experts use to assess and analyze possible risks. The information obtained during the research is based on the theoretical knowledge base and on practical experience in assessing the degree of risk for the Gaga board game store.